Aspek-Aspek Humanis Pemikiran Keagamaan Hamka - Titis Rosowulan (Jurnal Hikmatuna, 2015)
Problems of justification and the negative stigma on diverse religious thought is still a fundamental problem in the life of the nation. It is therefore not surprising that conflicts are emerging and it is not uncommon to take casualties. This was caused by religious understanding approach that emphasizes the attitude of truth claims. If the truth claims unilateral approach still adorn religious understanding, without any attempt to find common ground between people, the same conflicts will continue to recur and will possibly worsen. This study outlines the thinking humanism Hamka and relevance to religious thought in Indonesia. This study is one of the authors of ijtihad to reduce the occurrence of prolonged conflict and building bridges open dialogue in addressing religious understanding is different. The focus in this study is the concept of religious humanism and relevance Hamka Hamka humanism thinking against religious thought in Indonesia.